Early-Age Properties Development of Recycled Glass Powder Blended Cement Paste: Strengths, Shrinkage, Nanoscale Characteristics, and Environmental Analysis - He, Zhihai; Shen, Menglu; Shi, Jinyan; Chang, Jingyu; Gençel, Osman; Revilla-Cuesta, Victor; Gençel, Osman (Tech Science Press, 2023)
Recycling solid waste in cement-based materials cannot only ease its load on the natural environment but also reduce the carbon emissions of building materials. This study aims to investigate the effect of recycled glass powder (RGP) on the early-age mechanical properties and autogenous shrinkage of cement pastes, where cement is replaced by 10%, 20% and 30% of RGP. In addition, the microstructure and nano-mechanical properties of cement paste with different RGP content and water to binder (W/B) ratio were also evaluated using SEM, MIP and nanoindentation techniques. The results indicate that the early-age autogenous shrinkage decreases with the increase of RGP content and W/B ratio. While the mechanical strength deteriorates due to the addition of RGP, it can be compensated by reducing the W/B ratio. Although the addition of RGP increases the total porosity of the hardened paste, it reduces the small size porosity (<50 nm). In addition, the proportions of different types of C-S-H are changed, and the volume fraction of porosity is increased, but that of hydration products of cement paste is reduced due to the incorporation of RGP. Besides its pozzolanic activity, the mitigated shrinkage deformation that RGP is generating in cement pastes is encouraging for its use as a novel supplementary cementitious material that reduces the early-age cracking risk of cement-based materials. Meanwhile, the life cycle assessments indicate that the RGP-cement component is an economical and eco-friendly novel engineering material.
Keywords: Cement Paste; Waste Glass Powder; Autogenous Shrinkage; Microstructure; Nanoindentation